Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Karakter Peserta Didik Kelas VI SD - Gunawan, Putra; Apriani, Eka (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This study aims to determine the role of Islamic Religious Education teachers in instilling the character values of students to find out the methods, supporting and inhibiting factors faced in instilling character values at SD Negeri 004 Sei Sialang, especially class VI. This type of research is Field Reasearch, which is research that requires researchers to go to the 'field' to make observations about a phenomenon in a natural situation. The data sources used are primary data sources and secondary data sources. Data collection methods are interviews, observation and documentation. While the data analysis technique used is inductive through data reduction, data presentation (data display) and conclusions (verification). The conclusion obtained is that the role of Islamic Religious Education teachers in instilling character values in students can be through group activities with the hope of applying the character of discipline and responsibility. In addition, the application of 7s (smile, greeting, greeting, politeness, courtesy, patience and gratitude). Methods used in instilling character values can be through exemplary methods, advice methods, demonstration methods, and discussion methods. Supporting factors in instilling character values are supporting facilities and infrastructure and storytelling media, while inhibiting factors in instilling character values include parents' busyness, the environment, and mass media. Furthermore, the solution to overcome obstacles in instilling character values is giving assignments and cooperation between teachers and parents.